Satuan Lingual Batik Tulis Girilayu di Kabupaten Karanganyar - Mericha Astri Hastuti; Tommi Yuniawan (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Girilayu Village, Matesih District, Karanganyar Regency is one of the villages for hand-drawn batik craftsmen who still adhere to the heritage tradition. Girilayu written batik is rich in culture, which then contributes to the language treasury. The objectives of this study are (1) to describe the form of the lingual unit of Girilayu written batik in Karanganyar Regency; (2) identify the lexical meaning and cultural meaning in Girilayu batik in Karanganyar Regency. The theoretical approach used is ethnolinguistic studies and methodologically uses qualitative descriptive. Data collection uses listen and speak method. The data were analyzed using the agih method and the matching method. The results of data analysis are presented with formal and informal methods. From the results of this study, it was found that there were 68 findings of lingual units which were classified into 2 forms, namely word forms and phrase forms. The lingual units found in the form of words amounted to 34 data which were then divided into two forms, namely monomorphemic with 22 data and polymorphemic with 12 data. The form of phrases found a number of 33 lingual units.